2020
DOI: 10.1108/jfbm-08-2020-0079
|View full text |Cite
|
Sign up to set email alerts
|

Determining nonfamily employees' job satisfaction and turnover intentions: the roles of job autonomy and work passion

Abstract: PurposeThe purpose of this study seeks to examine how nonfamily employees' job autonomy and work passion can influence their job satisfaction and intention to quit in family small-to-medium-sized enterprises (SMEs). Current, research regarding the determinants of nonfamily employees' job satisfaction and turnover intentions has largely focused on the effects of family influence and family firm characteristics. Accordingly, not much is known of how the job characteristics and emotions of nonfamily employees inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 155 publications
(259 reference statements)
0
17
0
Order By: Relevance
“…Fear of COVID-19 positively correlates with turnover scores (Abd-Ellatif et al , 2021). Job autonomy could be another reason for the turnover intention of health-care workers during this pandemic; Mustafa et al (2020) found that job autonomy affects the intention to quit. Job autonomy enhances knowledge sharing, employee empowerment, team building and harmony.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Fear of COVID-19 positively correlates with turnover scores (Abd-Ellatif et al , 2021). Job autonomy could be another reason for the turnover intention of health-care workers during this pandemic; Mustafa et al (2020) found that job autonomy affects the intention to quit. Job autonomy enhances knowledge sharing, employee empowerment, team building and harmony.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…However, the main challenge facing this type of firm is how to ensure a balance between family system and business mindedness (Steier et al. , 2015; Contreras-Lozano et al ., 2022; Mustafa et al ., 2020). Unfortunately, the majority of family business founders lack the relevant business training (Carlsen et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Family business, defined as "a business governed and/or managed with the intention to shape and pursue the vision of the business held by a dominant coalition controlled by members of the same family or a small number of families in a manner that is potentially sustainable across generations of the family or families" (Chua et al, 1999, p. 25), is known to encounter financial challenges, cultural clashes between family and non-family members, and sometimes a lack of non-family members' engagement with its objectives (Berrone et al, 2012;Samara and Arenas, 2017;Knezovi c and Greda, 2021). However, the main challenge facing this type of firm is how to ensure a balance between family system and business mindedness (Steier et al, 2015;Contreras-Lozano et al, 2022;Mustafa et al, 2020). Unfortunately, the majority of family business founders lack the relevant business training (Carlsen et al, 2001).…”
Section: Family Businesses In the Egyptian Contextmentioning
confidence: 99%
“…A third explanation is that the owner is self-invested, for example has invested time, ideas, skills and intellectual energy into the organisation. Psychological ownership has been used to study topics such as job satisfaction and the work attitudes of non-family members (Sieger et al , 2011; Bernhard and O'Driscoll, 2011; Ramos et al , 2014; Erdem and Atsan, 2015; Mustafa et al , 2020), non-family CEO's contribution to financial and non-financial goals (Huybrechts et al , 2013), stewardship behaviour of CEOs (Henssen et al , 2014) or top management team members (Lee et al , 2019; Broekaert et al , 2018), and as a determinant of entrepreneurial orientation (Pittino et al , 2018).…”
Section: Literature Review and Theorymentioning
confidence: 99%